(untitled) (GAIMS Journal of Medical Sciences, 2024)
Lafora disease is rare group of progressive myoclonic epilepsies, worldwide. It is more common in children and adolescents and is genetic, glycogen metabolism disorder. It has Autosomal recessive (AR) inheritance and characterized by presence of inclusion bodies known as Lafora bodies within cytoplasm of cells in heart, liver, muscle, skin. Disease clinically has triad of seizures, myoclonus, and dementia. Lafora disease is a neurodegenerative disorder that causes impairment in the development of cerebral cortical neurons. In the absence of laforin function, long glucose chains in specific glycogen molecules extrude water form double helices and drive precipitation of molecules which accumulate into Lafora bodies. Onset of clinically usually starts in the range of 8-19 years of age and peaks around 15 years of age. In our case, 16-year-old girl presented to emergency of tertiary care hospital with complain of episode of convulsions 40 minutes before admission. She is known case of generalized tonic-clonic seizures for past two years. Axillary skin biopsy on H&E staining showed pilosebaceous glandular unit with peri-adnexal and perivascular infiltrate. PAS-D stain showed round, globular, tiny PAS positive material noted within sweat glands. MRI brain was suggestive of right vertebral artery partial occlusion.